PENINGKATAN KETERAMPILAN BERTANYA SISWA KELAS 2A SD MATERI PEDULI LINGKUNGAN BERBANTUAN MEDIA POP UP BOOK - Suaidah, Amida; Lilik Bintartik; Aldi Surya Kinasih; Alviena Tazky Amalia; Devi Restu Putpitasari; Hinggar Relung Puspita; Sinta Kiswoyo Putri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the low level of questioning skills among lower-grade students in the Pancasila Education subject. The research aimed to improve the questioning skills of Grade IIA students at SDN Bareng 3, Malang City, regarding the topic of "Environmental Care" through the use of pop-up book media. A Classroom Action Research (CAR) method utilizing the Kemmis and McTaggart model was implemented over three cycles. The research subjects consisted of 28 students (16 boys and 12 girls). Data collection was conducted through observation using a questioning skills assessment rubric, teacher activity observation sheets, and documentation. The results indicated an improvement in questioning skills across each cycle. The number of students actively asking questions rose from 9 in Cycle I to 11 in Cycle II, reaching 17 in Cycle III. The class average score also increased from 41.56 to 53.50, ultimately reaching 62.50 in Cycle III. The percentage of classical mastery rose from 3.70% to 18.52%, reaching 32.14% by the end of the study. Based on these findings, it can be concluded that the use of pop-up book media, combined with heterogeneous group discussions, is effective in enhancing students' questioning skills. This medium helps boost students' confidence in asking questions, reduces hesitation during communication, and trains them to formulate appropriate questions. Although classical mastery did not reach an optimal level, the research results demonstrated consistent progress in questioning skills throughout the implementation cycles